Dynamics and Literature Review of Malaria Cases in Indonesia in the Development of Diagnosis and Management in 2020-2025 - Putu Ristyaning Ayu Sangging; Shifa Tanjia Zahira TS; M. Mahdi Al Ayubi; Faizah Zahra Aurelia; Rasha Andhika Satria; Rangga Pratama Wahyuono Putra (Poltekkes Kemenkes Tanjung Karang, Indonesia, 2026)
Malaria remains a major public health problem in Indonesia, especially in eastern provinces such as Papua and West Papua. The period 2020–2025 is critical because it combines the national malaria elimination program with disruptions to health services during the COVID-19 pandemic. Understanding trends in diagnosis and clinical management is important to strengthen national strategies. This systematic review summarizes evidence on malaria trends in Indonesia from 2020 to 2025, focusing on diagnostic developments and treatment practices. A systematic search was conducted in PubMed, Scopus, Google Scholar, ScienceDirect, SINTA, and Garuda using keywords such as “malaria,” “Indonesia,” “diagnosis,” “management,” “RDT,” “microscopy,” “PCR,” and “ACT.” Articles published between January 2020 and February 2025 were screened using PRISMA guidelines. Studies were included if they reported malaria incidence, diagnostic methods, treatment strategies, or surveillance outcomes in Indonesia. Of 1,182 records identified, five studies met the final inclusion criteria. Data were extracted and analyzed narratively. The findings show that microscopy remains the gold standard for malaria diagnosis. However, its effectiveness is limited by uneven distribution of trained personnel and laboratory capacity. Rapid Diagnostic Tests (RDTs) are increasingly used in remote areas because they are practical and easy to use, although their sensitivity decreases in cases with low parasite levels. Polymerase Chain Reaction (PCR) offers better detection of low-density and mixed infections, but its use is largely restricted to research centers and tertiary laboratories. For treatment, Artemisinin-based Combination Therapy (ACT) remains the main therapy for uncomplicated malaria, while intravenous artesunate is the first-line treatment for severe cases. Across the reviewed studies, early diagnosis, appropriate use of antimalarial drugs, and reduction of mosquito exposure were consistently linked to better outcomes. Screening of students from endemic areas who were studying in non-endemic provinces did not detect asymptomatic malaria cases. Overall, the review shows both progress and ongoing challenges. Diagnostic capacity has improved, but regional disparities remain. Strengthening laboratory skills, better integrating RDT, microscopy, and PCR approaches, and improving surveillance and referral systems are essential to reach the 2030 malaria elimination target. Future research should focus on monitoring treatment response, mapping drug resistance, and evaluating the implementation of diagnostic strategies.